Anti-citrullinated protein antibodies have a low avidity compared with antibodies against recall antigens. Issue 2 (10th November 2010) - Suwannalai, P; Scherer, H U; van der Woude, D; Ioan-Facsinay, A; Jol-van der Zijde, C M; van Tol, M J D; Drijfhout, J W; Huizinga, T W J; Toes, R E M; Trouw, L A
Abstract : Objectives: Anti-citrullinated protein antibodies (ACPA) are highly specific for rheumatoid arthritis (RA) and have been implicated in disease pathogenesis. Recent ongoing evidence indicates that the ACPA response broadens before precipitation of full-blown RA, as indicated by a more extensive isotype usage and an increased citrullinated epitope recognition profile. Nonetheless, the evolution of the ACPA response is still poorly understood and might intrinsically differ from the protective responses against pathogens. Methods: The avidity and the avidity maturation of ACPA in relation to the avidity of antibodies against recall antigens were analysed. Results: The avidity of ACPA was significantly lower than the avidity of antibodies to the recall antigens tetanus toxoid and diptheria toxoid. Moreover, ACPA did not show avidity maturation during longitudinal follow-up and ACPA avidity was also relatively low in patients who displayed extensive isotype switching. Conclusions: These observations indicate that the natural evolution of ACPA differs from the development of antibodies against recall antigens. These data also indicate that ACPA avidity maturation and isotype switching are disconnected, whereby extensive isotype switching occurs in the setting of restricted avidity maturation. Intrinsic differences between the RA-specific autoantibody system and protective antibody responses against pathogens could be of relevance for designing novel B cell-targeted therapies for RA.